Effect of postal prompts to patients and general practitioners on the quality of primary care after a coronary event (POST): randomised controlled trial. Issue 7197 (5th June 1999) - Feder, Gene; Griffiths, Chris; Eldridge, Sandra; Spence, Matthew
Abstract: Objectives: To determine whether postal prompts to patients who have survived an acute coronary event and to their general practitioners improve secondary prevention of coronary heart disease. Design: Randomised controlled trial. Setting: 52 general practices in east London, 44 of which had received facilitation of local guidelines for coronary heart disease. Participants: 328 patients admitted to hospital for myocardial infarction or unstable angina. Interventions: Postal prompts sent 2 weeks and 3 months after discharge from hospital. The prompts contained recommendations for lowering the risk of another coronary event, including changes to lifestyle, drug treatment, and making an appointment to discuss these issues with the general practitioner or practice nurse. Main outcome measures: Proportion of patients in whom serum cholesterol concentrations were measured;proportion of patients prescribed β blockers (6 months after discharge); and proportion of patients prescribed cholesterol lowering drugs (1 year after discharge). Results: Prescribing of β bockers (odds ratio 1.7, 95% confidence interval 0.8 to 3.0, P>0.05) and cholesterol lowering drugs (1.7, 0.8 to 3.4, P>0.05) did not differ between intervention and control groups. A higher proportion of patients in the intervention group (64%) than in the control group (38%) had their serum cholesterol concentrations measured (2.9, 1.5 to 5.5, P<0.001). Secondary outcomes were significantly improved for consultations for coronary heart disease, the recording of risk factors, and advice given. There were no significant differences in patients' self reported changes to lifestyle or to the belief that it is possible to modify the risk of another coronary event. Conclusions: Postal prompts to patients who had had acute coronary events and to their general practitioners in a locality where guidelines for coronary heart disease had been disseminated did not improve prescribing of effective drugs for secondary prevention or self reported changes to lifestyle. The prompts did increase consultation rates related to coronary heart disease and the recording of risk factors in the practices. Effective secondary prevention of coronary heart disease requires more than postal prompts and the dissemination of guidelines.